Development and Validation of Reverse-phase High-performance Liquid Chromatography Method for Simultaneous Estimation of Riluzole and Levodopa in Tablet Dosage Form - Rudrapal, Mithun (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The objective of this study was to develop a new and simple reverse-phase high-performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of riluzole (RZ) and levodopa (LD) in the marketed tablet dosage form. Materials and Methods: The chromatographic separation was achieved on a RP hypercil C18 column (250 × 4.6 mm i.d., 5 μm) using a mobile phase consisting of methanol and water (75:25 v/v) at a flow rate of 1.0 ml/min with the ultraviolet detection wavelength of 273 nm at ambient temperature. The developed method was validated as per the International Council on Harmonization guideline for linearity, accuracy, precision, robustness, ruggedness, limit of detection (LOD), limit of quantitation (LOQ), and specificity. Results: Results of validation studies were found satisfactory with % relative standard deviation values of <2% indicating good specificity, validity, and reliability of the method. The method showed good linearity over the concentration range of 20–80 μg/ml with correlation coefficient (r2) values of 0.990and 0.999 for RZ and LD, respectively. The mean percentage recoveries were between 99.46–99.80% and 100.15–101.24% for RZ and LD, respectively. The LOD and LOQ values were found to be 0.036and 0.012 μg/ml, and 0.110and 0.036 μg/ml for RZ and LD, respectively. The assay of RZ and LD in the marketed tablet formulation was found to be 99.67and 98.95%, respectively. Conclusion: The RP-HPLC method is reported to be simple, specific, accurate, and precise. The proposed method can be successfully applied for the routine analysis of RZ and LD in the bulk drugs as well as in combined pharmaceutical dosage forms.